Total phenolics contents and free radical scavenging capacity of piper sarmentosum (pucuk kaduk) extract - Mat Jusoh, Hanapi; Haron, Normah; Mohd Zohari, Sarah Haryati (International Islamic University Malaysia, 2019)
Introduction: Piper sarmentosum is one of the herbaceous plants that has been used as natural antioxidant to source to treat diseases. This study was conducted to determine the total phenolic contents (TPC) and free radical scavenging capacity in free and bound (soluble and insoluble) of P. sarmentosum. Methods: Free phenolic extract was acquired through direct methanol extraction while acidic and alkaline hydrolyses were adopted to release the bound phenolic acids. The TPC was determined by using Folin-Ciocalteu assay and is expressed as Gallic Acid equivalent (GAE) in miligrams per gram of extracts. The antioxidant scavenging capacity was determined by using DPPH (2, 2-diphenyl-1-picrylhydrazyl) assay. Results: Insoluble bound phenolic extract of P. sarmentosum showed the highest TPC value (1.54 ± 0.04 mg GAE/g DW) followed by soluble phenolic extract and free extract (1.13 ± 0.10 and 0.57 ± 0.06 mg GAE/g DW, respectively). The soluble phenolic fraction has expressed the highest free radical scavenging capacity (76.57± 4.12%) followed by insoluble (69.79± 2.33